Generation Z, Disinformation, and Critical Digital Literacy: Strengthening National Identity in the Social Media Era - Firdaus, Rahmat; Millu, Patrisya Marthini Grasella; Fadhillah, Parsya; Ghaisani, Aisyah Hazhiyah; Attailah, Radit Zain (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Generation Z's knowledge exploration, interpretation of nationality, and existence as citizens are all influenced by social media, which has evolved beyond its original purpose of sharing news. Combining the emotional intensity of broadcasts with the impersonal nature of automated curation may lead to a loss of context and the polarization of public discourse. This study employs a qualitative literature review by examining scholarly sources published between 2015 and 2025. The analysis was carried out using a thematic synthesis approach to identify patterns, findings, and emerging trends related to disinformation, critical digital literacy, and national identity among Generation Z, This article presents a practical solution: bolstering Indonesian identity while simultaneously combating misinformation via the integration of critical digital literacy, algorithmic awareness, and digital nationalism. A review of research conducted between 2024 and 2025 highlights four important aspects: (1) misleading campaign videos with text often surface on social media platforms like Facebook, YouTube, and TikTok. (2) In order to combat this, schools should implement source verification assignments, encourage slow reading, and create data-based counternarratives. (3) To create an effective literacy the environment, teachers and librarians should prioritize frequent small sessions, literacy teams, student representatives, and interactive channels. (4) Gen Z is more likely to find meaningful cultural hashtags, local collections, historical site vlogs, and participatory national narratives. Thus, being tech-savvy is only the tip of the iceberg when it comes to digital literacy; it also serves as a glue for Indonesian identity and a foundation for public reason